An I6P7 peptide modified fluorescent probe for bio-imaging. (4th January 2019) - Yao, Yuxin; Gui, Lijuan; Gao, Beike; Yuan, Zhenwei; Chen, Yisha; Wei, Chen; He, Qing; Wang, Fei; Xu, Mingjun; Chen, Haiyan
Abstract : DMP exhibits high tumor cell affinity and favorable mitochondria-targeting capability.DMP exhibits high pH stability and good water-solubility. Abstract : The I6 P7 peptide was proved to specifically bind to the interleukin-6 receptor, which can be exploited as an effective tumor-targeting moiety. Herein, a novel tumor-targeting fluorescent probe (DMP ) conjugated with the I6 P7 peptide was designed and synthesized. This probe was validated to possess valuable photophysical properties. The biocompatibility was evaluated by investigating its cytotoxicity on HUVEC and U87 cells, respectively. The tumor cell affinity has been confirmed by bio-imaging of this probe on different human cancer cells (U87, A549 and MCF-7 cells) and normal cells (HUVEC cell). The probe demonstrates low cytotoxicity, high tumor cell affinity and favorable mitochondria-targeting capability. Overall, these results revealed thatDMP can serve as an important fluorescent probe for tumor-targeted bio-imaging.